DC distribution system on vessels and stability analysis - Zhou, Jingjie (2019)
Currently, most vessels adopt an onboard AC power distribution system. DC distribution system is proposed to be installed on offshore vessels aiming to save fuel and increase the working efficiency on ships, even though the technology is still under evaluation with several challenges to be encountered. In this report, the benefits of adopting the DC power transmission system will be outlined. The DC distribution system on vessels will be introduced in the first part, including its main components, which refers to generators, converters, inverters, rectifiers, battery system, and motors. Meanwhile, the DC distribution system stability issue, which needs to be taken into consideration during operation will be covered, such as system oscillations and resonance. Consequently, stability issues of the system will be covered in the second part, including fundamental conceptions, such as CPLs and EPS. Furthermore, several criterions assessing stability problems will be included. Finally, future work should be concentrated on how the artificial conservativeness that exists among the criterion can be minimized.